(untitled) (Journal of Computational Mathematics, 2021)
Many types of nonlinear systems can be solved by using ordered iterative methods. These systems are discussed in [2] in a unified form for five different initial conditions. This paper is a continuation of [2]. Under arbitrary initial conditions, some iterative methods are given, and several theorems for the existence and uniqueness of the solution and convergence of the methods are proved.